Effect of integrated use of Zircon and Siliplant on productivity of Echinacea purpurea roots in Western Caucasus - R. R. Thaganov; N. I. Sidelnikov (Овощи России, 2024)
Echinacea purpurea L. – is a perennial medicinal plant, from the herb of which dozens of preparations have been created that are used to strengthen the immune system, in the treatment of inflammatory diseases. At present, oxyconic acids and alkamides have been found in the plant’s root system, and the preparations «Anginol» and «Prostanov» have been created on their basis. The production and creation of new medicinal products from the roots and rhizomes of the Echinacea purpurea depends on a stable raw material base, which can be ensured by obtaining maximum yields of roots. As a result of studies to determine the timing of harvesting, methods to increase the yield of the underground mass in the conditions of the Krasnodar Territory, it was revealed that the high yield of roots and rhizomes of Echinacea purpurea was determined on plantations III-IV years of growing, which averaged 10 c/ha, they had an oxyconic acid content of 3,9%. In the future, there is a decrease in yield to 8 c/ha, and active substances to 2.1%. Dual treatments treatments Zircon (0.04 l/ha) and Siliplant (0.5 l/ha) both separately and in the mixture gave the opportunity to increase the yield for III and IV years to 28–30% and improve the quality of raw materials, the content of active substances increased by 5–7%. The complex use of these drugs in the V year of vegetation allows to increase the yield of roots to 10.3 c/ha with a high content of oxidic acids – 2.55%. It was revealed that foliar fertilization of vegetative plants with two-component system Siliplant + Zircon promotes the adaptation of Echinacea purpurea to dry weather conditions and makes it possible to obtain stable yields of medicinal raw materials with high quality regardless of weather conditions.